2007
DOI: 10.1152/ajpendo.00316.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of ornithine decarboxylase in the mouse adrenal: influence of polyamine deprivation on catecholamine and corticoid levels

Abstract: Bastida CM, Cremades A, Castells MT, López-Contreras AJ, López-García C, Sánchez-Mas J, Peñ afiel R. Sexual dimorphism of ornithine decarboxylase in the mouse adrenal: influence of polyamine deprivation on catecholamine and corticoid levels. Am J Physiol Endocrinol Metab 292: E1010 -E1017, 2007. First published December 5, 2006; doi:10.1152/ajpendo.00316.2006.-Adrenal sexual dimorphism is thought to be important in explaining sex-related differences regarding prevalent diseases and the responses to stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…The opposite effect of testosterone on DDC gene expression found in kidney and intestine could be related, in principle, with differences in the set of nuclear receptor co-repressors or co-activators or in other tissue-specific factors, as well as in epigenetic changes that may affect androgen action. In this regard, it must be noted that opposite effects of testosterone on other amino acid decarboxylases, such as ODC, have been also observed in different mouse tissues, where androgens dramatically increased this enzyme in the kidney but down-regulated ODC in the mouse adrenals (Bastida et al 2007). Furthermore, our results on the effect of androgens on renal DDC are in agreement with recent studies that concluded that human neoplastic prostate epithelium DDC is down-regulated by androgens (Nelson et al 2002).…”
Section: Discussionsupporting
confidence: 92%
“…The opposite effect of testosterone on DDC gene expression found in kidney and intestine could be related, in principle, with differences in the set of nuclear receptor co-repressors or co-activators or in other tissue-specific factors, as well as in epigenetic changes that may affect androgen action. In this regard, it must be noted that opposite effects of testosterone on other amino acid decarboxylases, such as ODC, have been also observed in different mouse tissues, where androgens dramatically increased this enzyme in the kidney but down-regulated ODC in the mouse adrenals (Bastida et al 2007). Furthermore, our results on the effect of androgens on renal DDC are in agreement with recent studies that concluded that human neoplastic prostate epithelium DDC is down-regulated by androgens (Nelson et al 2002).…”
Section: Discussionsupporting
confidence: 92%
“…To ascertain this, a separate restraint stress experiment was carried out to evaluate the hypothalamus-pituitary-corticoadrenal axis (HPA). Female mice showed higher adrenal gland and stress circulating corticosterone levels than male mice, as expected [45,46]. Muscle IL-6 KO female mice responded less to restraint stress, in principle ruling out sensitivity to stress as the main reason underlying the differences in body weight during the acclimatization periods of the fasting/refeeding-leptin experiments.…”
Section: Discussionsupporting
confidence: 72%
“…The major rate-limiting enzymes of this pathway are ornithine decarboxylase (ODC), spermidine/spermine N 1 -acetyl transferase (SAT1), and S-adenosylmethionine decarboxylase (AMD1), whose activities are influenced by numerous regulatory proteins as well as the polyamine levels [9]. In addition, not only are polyamines known to influence neurotransmitter systems, such as catecholamines [10,11], gamma-aminobutyric acid (GABA) [12], glutamate [13], and nitric oxide [14], but agmatine is also believed to act as a neurotransmitter [15]. Finally, polyamines are also able to influence the properties of several transmembrane channels, thereby affecting cell excitability [16].…”
Section: -Biosynthesismentioning
confidence: 99%